Coronary artery disease and cardiovascular outcomes in patients with type 2 myocardial infarction. (14th October 2021) - Taggart, C; Wereski, R; Bularga, A; Mills, N L; Chapman, A R; ,
Abstract: Purpose: To evaluate the role of coronary disease in predicting adverse cardiovascular events in patients with type 2 myocardial infarction. Background: Type 2 myocardial infarction occurs due to imbalance in myocardial oxygen supply or demand without atherothrombosis. There is currently no consensus on how patients with type 2 myocardial infarction should be investigated or treated. Although non-cardiovascular mortality is common in this population, the incidence of future cardiovascular events is similar to those with myocardial infarction due to plaque rupture. Observational data suggest patients with type 2 myocardial infarction and underlying coronary artery disease may be at higher risk of cardiovascular events, but to date, most findings have been observed in selected rather than consecutive patient cohorts. Methods: We conducted a secondary analysis of a multi-centre randomised controlled trial of 48, 282 consecutive patients attending hospital with suspected acute coronary syndrome. In 9, 115 patients, high-sensitivity cardiac troponin concentrations were >99th centile, and the diagnosis was adjudicated in line with the Fourth Universal Definition. Patients with type 2 myocardial infarction were stratified by the presence of previous coronary artery disease and evaluated for a primary outcome of cardiovascular death or Type 1 or 4b myocardial infarction at one year. Competing risk cox regression models were used to evaluate predictors of the primary outcome selected a priori on the basis of clinical importance, with adjustment for the competing risk of non-cardiovascular death. Results: The diagnosis of type 1 and type 2 myocardial infarction was made in 55% (4, 981) and 12% (1, 121) of patients, respectively. Compared to patients without a previous diagnosis of coronary artery disease, those with coronary disease were older (78 vs 71) and more likely to be female (54% vs 46%). The incidence of future cardiovascular death or myocardial infarction was highest in patients with type 2 myocardial infarction and previous coronary disease (20%, 91/454), compared to those with type 2 myocardial infarction without known coronary disease (10%, 69/667, P<0.001), and was similar to patients with type 1 myocardial infarction (17%, 863/4981, Figure 1). After adjusting for cardiovascular risk factors, the presence of known coronary disease remained an important predictor for future cardiovascular death or myocardial infarction (adjusted Hazard Ratio 1.45, 95% confidence interval 1.03 to 2.03; Figure 2). Conclusion: Coronary artery disease is an independent predictor of cardiovascular outcomes in patients with type 2 myocardial infarction. Further research is required to evaluate whether systematic investigation for coronary artery disease and targeted secondary prevention could improve outcomes in patients with type 2 myocardial infarction. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation